VR Digital Concert / Muhammad Azeem Ibrahim … [et al.] - Ibrahim, Muhammad Azeem; Abdul Manan, Muhammad Fakhrullah Aizat; Mohd Nizam, Nurain Khadijah; Zulkarnain, Nurul Akma; Thonghom, Thippayaporn (2022)
Virtual Reality Concert is a technology that allows people to experience a live concert while feeling immersed in their surroundings. This environment is viewed through a device known as a Virtual Reality headset or helmet. Normally, people use a VR headset for gamification, but it can also be used for other forms of entertainment, such as a virtual concert. Even, many concerts were cancelled due to pandemic Covid-19 and other issues such as the death of an actress and most people are concerned about crowded places. The digital concert can provide more entertainment to anyone who wants to participate and can be used wherever you want and enjoyed without interruptions. In addition, it can be used at home along Covid-19. Besides, to make the digital concert more interesting, we have included hologram technology for attendees and singers to gain new experiences from watching and performing in the concert. Last but not least, with virtual reality concerts and hologram technology, people can join the concert and enjoy it wherever they want.